Soviet-Tuvan fellowship during the Great Patriotic War of USSR against fascist Germany - Mollerov, Nikolay M. (The New Research of Tuva, 2010)
Article is composed of the text of author’s report on round table “Victory of Soviet people over the fascist Germany is a victory of Tuvan people as well”, that took place on April 30, 2010 at the Tuvan Institute for Humanitarian Researches marking the 65th anniversary of the Great Victory.
Keywords: war; history; USSR; Tuvan people; People’s Republic of Tuva; Tuva; mission; government; delegacy